The JAMM motif of human deubiquitinase Poh1 is essential for cell viability - Gallery, Melissa; Blank, Jonathan L; Lin, Yinghui; Gutierrez, Juan A; Pulido, Jacqueline C; Rappoli, David; Badola, Sunita; Rolfe, Mark; Macbeth, Kyle J (Molecular cancer therapeutics, 2007)
Poh1 deubiquitinase activity is required for proteolytic processing of polyubiquitinated substrates by the 26S proteasome, linking deubiquitination to complete substrate degradation. Poh1 RNA interference (RNAi) in HeLa cells resulted in a reduction in cell viability and an increase in polyubiquitinated protein levels, supporting the link between Poh1 and the ubiquitin proteasome pathway. To more specifically test for any requirement of the zinc metalloproteinase motif of Poh1 to support cell viability and proteasome function, we developed a RNAi complementation strategy. Effects on cell viability and proteasome activity were assessed in cells with RNAi of endogenous Poh1 and induced expression of wild-type Poh1 or a mutant form of Poh1, in which two conserved histidines of the proposed catalytic site were replaced with alanines. We show that an intact zinc metalloproteinase motif is essential for cell viability and 26S proteasome function. As a required enzymatic component of the proteasome, Poh1 is an intriguing therapeutic drug target for cancer.